Designing a Project-Based Curriculum Model in the Blended Learning System of the Second Cycle of Primary Education - Soltani, Mojtaba; Mehdizadeh, Amirhosein; Araghieh, Alireza; Shafiee, Nahid; Faghih Aram, Batoul (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to design a project-based curriculum model within the blended learning system of the second cycle of primary education. The qualitative findings of this study indicated that the core category of the research is “project-based learning in a blended learning system,” which comprises three main components: (1) structural flexibility, (2) digital constructivism, and (3) learning in a real-world context. The quantitative findings also confirmed a good model fit, such that the indices χ²/df < 3, RMSEA = 0.06, CFI = 0.93, and GFI = 0.91 were validated. Furthermore, the composite reliability of the components exceeded 0.70, and convergent validity (AVE > 0.50) was at an acceptable level. The final model of the study indicates that the successful implementation of a project-based curriculum in a blended learning environment requires teacher empowerment, reform of the assessment system, strengthening of technological infrastructure, and redefining the teacher’s role as a learning facilitator. The expected outcomes of this model include increased deep learning, creativity, responsibility, thinking skills, and a reduction in the gap between school and real-life contexts.